The design of viscometer with smartphone controlling - Ibragim E. Suleimenov; Grigoriy A. Mun; Sherniyaz B. Kabdushev; Adilet Alikulov; Dina B. Shaltykova; Inabat Moldakhan (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
New design of a viscometer based on the s tokes viscosity measurement method is proposed. The principle of operation of this viscosimetr is based on the use of ball periodic alternated movement in a horizontally positioned cuvette that filled with the test liquid. The movement appears under the in fluence of a magnetic field that created by two electromagnets. Registration of the ball movement inside the cuvette is carried out using an optoelectronic pair. A distinctive feature of the proposed design is control by using a program that installed on t he user's smartphone, which also carries out the primary data processing. Data transmission is carried out over the radio channel using a Bluetooth module. Disposable cuvettes are used for measurements. This approach makes it possible to significantly redu ce both the device production costs and operating costs by eliminating most of the operations for the device preparing for working (the vast majority of existing types of viscometers require thorough flushing of all units in contact with the test medium). In addition, the proposed approach excludes the occurrence of measurement errors associated with insufficiently thorough preparation of the device for operation.